2021
DOI: 10.1111/imj.15191
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of idiopathic pulmonary fibrosis complicating Type 2 diabetes: the Fremantle Diabetes Study Phase I

Abstract: During 106 865 person‐years of follow up, 17 (1.3%) Fremantle Diabetes Study Phase I participants with Type 2 diabetes and 57 (1.1%) matched individuals without diabetes developed idiopathic pulmonary fibrosis (IPF), an incidence rate ratio (95% confidence interval) of 1.40 (0.76–2.44) (P = 0.22). In the diabetes cohort, age at diabetes diagnosis and total serum cholesterol (inversely) predicted incident IPF in competing risk multivariable models. The incidence of IPF was low in community‐based cohorts, regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It could be related to the phenomenon of paradoxical obesity. In this way, in people with diabetes, overweight has been associated with a lower risk for in-hospital mortality [45]. It is also possible that patients with diabetes are admitted to the hospital more frequently than patients without diabetes with the same clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…It could be related to the phenomenon of paradoxical obesity. In this way, in people with diabetes, overweight has been associated with a lower risk for in-hospital mortality [45]. It is also possible that patients with diabetes are admitted to the hospital more frequently than patients without diabetes with the same clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present meta-analysis, it was revealed that the prevalence of diabetes was increased markedly in IPF cases compared with controls, which suggests that DM and IPF might be positively associated. However, we noticed that a latest study [ 31 ] came to the opposite conclusion. Since all of the included studies are retrospective case–control studies, which are easily affected by recall bias and additionally, the interpretation of the outcome is in the limitation of the significant heterogeneity, which could not be satisfactorily explained, we believe that our conclusion still need further evidence.…”
Section: Discussionmentioning
confidence: 71%
“…This may be attributed to either the occurrence of cardiovascular mortality prior to the development of IPF in patients with diabetes or the prolonged survival of patients with coexisting diabetes and IPF [ 23 ]. Another population-based case-control study reported that the incidence of IPF was higher in individuals with T2D compared to non-T2D population (incidence rate ratio = 1.40, 95% CI = 0.76–2.44, P = 0.22), although this difference did not reach statistical significance [ 24 ]. Notably, the level of glycemic control was not mentioned among participants with T2D in the original study.…”
Section: Discussionmentioning
confidence: 99%